2009
DOI: 10.1080/13811110802572221
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Autopsy Study of Suicidal Hanging from Cuttack, India: Focus on Stressful Life Situations

Abstract: Factors and stressful life situations associated with suicidal hanging in a sample from India were studied with a view to explore preventability. Information was collected on consecutive suicidal hanging victims in a 2-year period from various sources including family members through psychological autopsy method. Out of 662 autopsies involving suicide during the study period, 104 had used hanging as the method. Age group of 21-30 years, married females, unmarried males, dowry related stress, unemployment, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 11 publications
2
52
0
1
Order By: Relevance
“…Recent work (Wang & Stora, 2009) found evidence of psychiatric or drug disorders in 61% of suicides in the Faroe Islands, and work from China found a 'startlingly' low rate of mental disorder among completers (Law & Liu, 2008). Research in India also found a low rate of mental disorder, but a high rate of 'stresses stemming from social practices and perceptions' among completers (Vijayakumar et al, 2005;Jacob, 2008, Bastia & Kar, 2009). Of women from Goa who attempted or completed suicide, Maselko & Patel (2009) found mental disorder in 37% of cases, but significantly higher levels of exposure to violence and recent hunger.…”
Section: Notion: Not All Suicide Is the Results Of Mental Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work (Wang & Stora, 2009) found evidence of psychiatric or drug disorders in 61% of suicides in the Faroe Islands, and work from China found a 'startlingly' low rate of mental disorder among completers (Law & Liu, 2008). Research in India also found a low rate of mental disorder, but a high rate of 'stresses stemming from social practices and perceptions' among completers (Vijayakumar et al, 2005;Jacob, 2008, Bastia & Kar, 2009). Of women from Goa who attempted or completed suicide, Maselko & Patel (2009) found mental disorder in 37% of cases, but significantly higher levels of exposure to violence and recent hunger.…”
Section: Notion: Not All Suicide Is the Results Of Mental Disordermentioning
confidence: 99%
“…Not all suicide is the result of mental disorder, and this can be substantiated by recent population (Wang & Stora, 2009;Law & Liu, 2008;Jacob, 2008, Bastia & Kar, 2009Maselko & Patel, 2009) and individual (Cheah et al, 2008;Pridmore & McArthur 2008, 2009Pridmore 2009) studies.…”
Section: Synthesismentioning
confidence: 99%
“…The results from this study suggest that having children can actually be associated with suicide in those who have high levels of conflict with one or more children or who have stressors related to custody. Much of the previous research on the effect of family conflict on adult suicide has focused on conflict between romantic partners (e.g., Bastia and Kar 2009;Gururaj et al 2004; see Frey and Cerel 2015 for review). Though parents in our sample reported similar findings, their statements also highlight that conflict with children can be a predictor of future suicide attempts among some parents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked several family-related factors, such as stressful or traumatic life events (Bastia and Kar 2009) and domestic violence (Hawton et al 1996) to an increased risk for suicide. In fact, the tasks of parenting have also been suggested as increasing suicide risk.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide surveillance data currently are too frequently limited by a focus on rates, demographic features (Milner, McClure & De Leo, 2010) and diagnostics. They do not adequately consider the context and motivation of underlying problems and perceived causes or critically evaluate the impact of help seeking (Bastia & Kar, 2009). Influential accounts of suicide illustrate the point.…”
Section: Practical Implications For Preventionmentioning
confidence: 99%